Beekeeping: Watermelon Pollination - Malcolm T. Sanford; Jamie Ellis (EDIS)
In an effort to more widely disseminate information on optimizing watermelon pollination, this paper presents an overview of the introductory material on honey bee management and the section on pollination agreements and services in "Crop Pollination by Bees" by Keith S. Delaplane and Daniel F. Mayer.